2004
DOI: 10.1007/s00441-003-0837-7
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of alkaline phosphatase activity in aged human osteogenic periodontal ligament fibroblasts exhibiting short telomeres

Abstract: The osteogenic cell type of human periodontal ligament fibroblasts (PDLF) undergoes senescence at finite population doubling numbers unrelated to donor ages. This study investigated telomere lengths of osteogenic PDLF from differently aged donors and alterations of the osteoblast-like properties in the aged PDLF with short telomeres. Telomere lengths of osteogenic PDLF were biased towards long or short among all 15- to 51-year-old individuals, and did not show a normal distribution by Pearson's test or a corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…1B). In support of this and mirroring the data of the present study, in vitro experiments in human periodontal ligament cells showed an age-dependent reduction of alkaline phosphatase specific activity (14). One might speculate that the apparent discrepancy between the decrease in ALP activity (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…1B). In support of this and mirroring the data of the present study, in vitro experiments in human periodontal ligament cells showed an age-dependent reduction of alkaline phosphatase specific activity (14). One might speculate that the apparent discrepancy between the decrease in ALP activity (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…(72). In addition, the telomere length of osteogenic PDL cells did not show correlation with donor age, but did correlate with a reduction in alkaline phosphatase activity (83). Therefore, donor age seems to affect the in vitro life span of PDL fibroblasts.…”
Section: Factors Influencing Pdl Behavior In Vitromentioning
confidence: 99%
“…This however does not lead to an accumulation of senescent cell populations in the periodontal ligament of aged donors as Sawa et al [17] showed. Moxham and Evans [18] even found ultrastructural changes in periodontal ligament cells from aged animals indicating a decrease in collagen producing activity.…”
Section: Introductionmentioning
confidence: 99%